Hubungan Indonesia-Australia - Sarkawi B. Husain (Universitas Hamzanwadi, 2023)
Indonesia and Australia are two countries that have long historical and diplomatic relations. Unfortunately, studies on these various relationships, both in the journals and books, are very limited. Therefore, this book is very important to help us understand relationship between the two countries. This book give an important contribution in adding to the collection of important works about Australia written in Indonesian. This book explains how Australian foreign policy in general grew out of Australia's concerns and beliefs (or perceptions), and how it came to shape and develop further. This is supported by the author's careful and systematic explanation of the social context in which the basic assumptions underlying Australia's foreign policy are formed. Today, Indonesia-Australia relations are very close. Several programs were initiated such as Economic Management, Infrastructure, Water, Sanitation, and Hygiene. By collaborating with a number of institutions of the Government of the Republic of Indonesia, the Australian government helps to promote strong economic growth, sustainable economic growth that can be enjoyed by all people.Indonesia dan Australia adalah dua negara yang memiliki hubungan sejarah dan diplomatik yang cukup panjang. Sayang sekali, kajian-kajian tentang berbagai hubungan tersebut, baik dalam bentuk jurnal maupun buku tidak banyak dilakukan. Oleh karena itu, buku ini sangat penting untuk membantu kita memahami hubungan antara kedua negara. Buku ini memberi kontribusi penting dalam menambah koleksi karya penting tentang Australia yang ditulis dalam Bahasa Indonesia. Buku ini menjelaskan bagaimana kebijakan luar negeri Australia secara umum tumbuh dari kekhawatiran dan kepercayaan (atau persepsi) Australia, dan bagaimana ia kemudian terbentuk dan berkembang lebih jauh. Hal ini didukung oleh penjelasan cermat dan sistematis dari penulis atas konteks sosial di mana asumsi-asumsi dasar yang mendasari kebijakan luar negeri Australia terbentuk. Dewasa ini, hubungan Indonesia-Australia sangat dekat. Beberapa program digagas seperti Tata Laksana Ekonomi, Infrastruktur, Air, Sanitasi, dan Kebersihan. Dengan bekerjasama dengan sejumlah isntitusi Pemerintah Republik Indonesia, pemerintah Australia membantu untuk mempromosikan pertumbuhan ekonomi yang kuat, sustain serta dapat dinikmati oleh semua pihak.